Elevated activity of the large form of ADAR1 in vivo: Very efficient RNA editing occurs in the cytoplasm - WONG, SWEE KEE (Copyright 2003 by RNA Society, 2003)
Mammalian cells express small and large forms of the RNA editing enzyme ADAR1, referred to as ADAR1-S and ADAR1-L, respectively. Here we observed that ADAR1-L was >70-fold more active than was ADAR1-S when assayed with a substrate that could be edited in either the nucleus or cytoplasm, and was also much more active when assayed with a substrate that was generated in the cytoplasm during viral replication. In contrast, when a substrate that could only be edited within the nucleus was assayed, the activity of ADAR1-S was found to be somewhat higher than that of ADAR1-L. We show here not only that editing could occur in the cytoplasm but also that the process was extremely efficient, occurred rapidly, and could occur in the absence of translation. Consistent with the observation that editing in the cytoplasm can be very efficient, deletion of the nuclear localization signal from ADAR2 resulted in a protein with 15-fold higher activity when tested with a substrate that contained an editing site in the mature message. In addition to its potential role in an antiviral response, we propose that ADAR1-L is the form primarily responsible for editing mRNAs in which the editing site is retained after processing.